Analysis of correlation between real degradation data and a carbonation model for concrete structures. (January 2019) - Benítez, Pablo; Rodrigues, Fernanda; Talukdar, Sudip; Gavilán, Sergio; Varum, Humberto; Spacone, Enrico
Abstract: Over the past few decades, climate change has become a significant problem, the ramifications of which are of concern around the world. Global warming is a long-term process caused by phenomena such as increased levels of carbon dioxide (CO2 ) concentration in the atmosphere, increases in rainfall, changes in relative humidity and changes in temperature. Thus, this will aggravate the degradation process of reinforced concrete (RC) structures, leading to the decrease of durability, safety and serviceability. Regarding the durability of concrete structures, carbonation-induced corrosion is definitely a significant and costly source of degradation, directly related to climatic parameters such as CO2, temperature and relative humidity. In Paraguay, the lack of control during the construction of buildings often leads to weak structures highly vulnerable to the attack of harmful external agents. Therefore, this paper seeks to provide an analysis of the correlation between real degradation data and a numerical carbonation model for concrete structures in the country. According to the Intergovernmental Panel on Climate Change (IPCC) reports, climatic parameters will increase in the future. For this reason, an analysis of the decreasing performance of these structures caused by climate change will be addressed in this paper. This research aims to choose the most accurate mathematical model that can be applied in Paraguay for the prediction of the service life of concrete structures subjected to carbonation-induced corrosion. For that purpose, parameters and variables of the selected model have been defined and subsequently validated through carbonation tests results carried out in a set of RC structures built in the country. The results of this paper should be considered as a first stage for the further formulation of maintenance strategies, which is highly necessary for Paraguay.